Communication Strategies of Product-Harm Crises via Social Media: A Case Study on Samsung and Apple - Salem, Shaymaa; Elkhattat, Dina (The Arab Journal of Administration, 2019)
Facing crises is one of the critical challenges for any organization, and most of these crises related to the efficiency and effectiveness of its internal and external communication. Nowadays, the challenges increased with the broad use of social media, which provide a new pattern of communication, with its interactive characteristics. In this context, the study examines the communication strategies of the product-harm crises via social media to shed light on its positive and negative sides during times of crisis. The purpose of this study is to shed light on the concept of crisis communication through social networks in terms of concept, importance, characteristics, strategies, negatives, and the most important theoretical approaches. The study is based qualitative approach in the analysis, by reviewing two case studies (Apple and Samsung), they are the leading companies in manufacturing smartphones worldwide, and they faced Product-Harm Crises recently. The analysis focused on their communication responses and practices via social media. The results showed that social media changed the landscape of crisis communication. Therefore, organizations no longer have a choice about whether to integrate social media into crisis communication; the only choice is how to do so. Moreover, the findings indicated that the severity of Product-Harm Crises might increase according to the type of products, and the degree of its importance among customers, and to what extent these products related to their security, as the case of smartphones. In this context, the researchers developed a model in an attempt to conclude a set of lessons learned from the review of the theoretical framework and case studies. The model is explaining how to use communications strategies in line with the organization›s position on the crisis, as well as the recommended methods and procedures, especially in Product-Harm Crises.